PENGARUH TEKNIK PROBING PROMPTING TERHADAP PENINGKATAN HASIL BELAJAR MATEMATIKA SEKOLAH DASAR (STUDI EKSPERIMEN KUASI SISWA KELAS V SD NEGERI 184 PEKANBARU) - Rahmat Putra; Gustimal Witri; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: One of factor that influence low students achievement that was students hard to understand math material subject. Students do not understand the concepts in a material. That's why the author need to did the research by Probing Prompting. This learning technique is able to able to improve direct communication with teachers in developing new knowledge that can improve students' mathematics learning outcomes, especially on the material properties of flat wake. The main objective of this study is to examine the improvement of mathematics learning outcomes among students who obtain Probing Prompting learning through techniques with students who got conventional learning. This research was conducted in SDN 184 Pekanbaru in class Vb as the control class and class Va as a class experiment with using the method Nonequivalent Control Group Design. Result data were analyzed using t test with significance level α = 0.05. The results of the data analysis, based on the t-test average difference thitung = 1.946 with ttable = 1.995 and students achievement in the experimental class earned an average of 59.4 became 83.05 on the average score of the posttest. While the control group gained an average of pretest of 58.5 become to 76.9 from an average of the posttest. The results of this study indicate that there are differences in the average at the beginning of the test and the final test. Correlational test can be obtained from r = 0.655, the value of the correlation coefficient determinant (r2) was 0.43 meaning that the effect of applying the technique Probing Prompting the mathematics students achievement is 43% while 57% are influenced by other factors contained in the self and the environment these students. The result of this research showed that there was different average from both of classes but based on statistic there was no difference toward increase students achievement math between students who got Probing Prompting learning techniques with students who got conventional learning.Keywords: Technique Probing Prompting, Students Achievement